PEMIKIRAN PENDIDIKAN ISLAM SYEKH SULAIMAN ARRASULI DAN KITAB KLASIKNYA - Zulkifli Zulkifli (Turast: Jurnal Penelitian dan Pengabdian, 2015)
This article elaborated on the Islamic educational thought of Sheikh Sulaiman Arrasuli or known as InyiakCanduang. Shaykh Sulayman Arrasuli was an Islamic education leaders as one of “Kaum Tuo”, a group ofscholars who try to maintain local traditions without banging with the Islamic teaching. This group of scholarsis usually perceived as a traditional circles that are not in line with the ideas of progress. This study wanted torefute the common perception that develop in the community. In this study can be found that although InyiakCanduang was a traditionalist, but that does not mean he was anti-progress, even his thoughts were moreprogressive, although he concepted from clasical books. In this case, he is a smart scholar in dialogue betweentraditions, religions, and the demands of the era.